A companion to the American novel - Bendixen, Alfred (Hoboken, NJ : John Wiley & Sons, 2012)
Featuring 38 essays by distinguished literary scholars, A Companion to the American Novel provides a comprehensive single-volume treatment of the development of the novel in the United States from the late 18th century to the present day. Represents the most comprehensive single-volume introduction to this popular literary form currently availableFeatures 38 contributions from a wide range of distinguished literary scholarsIncludes essays on topics and genres, historical overviews, and key individual works, including The Scarlet Letter, Moby Dick, The Great Gatsby, Beloved, and many more.
Front Matter -- Historical Developments. The Development of the American Novel: The Transformations of Genre / Alfred Bendixen -- The American Novel: Beginnings through the American Renaissance / Maria Karafilis -- The American Novel: Realism and Naturalism (1860b6(B1920) / Jeanne Campbell Reesman -- Modernism and the American Novel / Peter L Hays -- Beyond Modernism: The American Novel between the World Wars / Alfred Bendixen -- The Cold War Novel: The American Novel between 1945b6(B1970 / Sharon Becker, Wendy Martin -- The Novel in a Changing America: Multiculturalism and other Issues (1970-Present) / Martha J Cutter -- Genres and Traditions. Fear, Ambiguity, and Transgression: The Gothic Novel in the United States / Charles L Crow -- The American Historical Romance: From James Fenimore Cooper and Nathaniel Hawthorne to Toni Morrison, Louise Erdrich, and E.L. Doctorow / Emily Miller Budick -- Making this whole Nation Feel: The Sentimental Novel in the United States / Marianne Noble -- Social Protest, Reform, and the American Political Novel / Chip Rhodes -- The American War Novel Tradition and the Individual Soldier / James H Meredith -- From the Sublime to the Ridiculous: Comic Traditions in the American Novel / Judith Yaross Lee -- Plotting a way Home: The Jewish American Novel / Derek Parker Royal -- Chicano/a Traditions in the American Novel / Juan J Alonzo -- African American Traditions and the American Novel / Melvin Donalson -- The American Novel of Mystery, Crime, and Detection / Leonard Cassuto -- O Brave New Worlds: Science Fiction and the American Novel / Eric S Rabkin -- Dreaming of a White Future: Mary E. Bradley Lane, Edward Bellamy, and the Origins of the Utopian Novel in the United States / Jean Pfaelzer -- Queer Theory and the American Novel / Deborah Carlin -- The American Short-Story Cycle: Out from the Novel's Shadow / Robert M Luscher -- Major Texts. The Woman's Law in Hawthorne's / Monika Elbert -- Writ in Water: The Books of Melville's / Wyn Kelley -- Wonder of Wonders: Harriet Beecher Stowe's / Susan Belasco -- Citational Strategies and Literary Traditions: Placing Henry James's / Greg W Zacharias -- Mark Twain's : A Child's Search for Comfort and Peace / Michael J Kiskis -- What Women want: Kate Chopin's / Emily Toth -- Private Fleming's Various Battles: Stephen Crane's / James Nagel -- Lily's Story: Edith Wharton's / Kathy Fedorko -- The Confessional Narration of Ernest Hemingway's / James Nagel -- Fitzgerald's and the Myth of the Land / Richard Lehan -- Ground Zero: Faulkner's / Philip Weinstein -- A Bigger Vision: Richard Wright's and the Great American Novel / Andrew Warnes -- Our : The Aesthetic Genealogy of US Diversity / John Carlos Rowe -- The Visionary Exuberance of Saul Bellow's / Ben Siegel -- The Flesh and the Word: Toni Morrison's / Valerie Smith -- A Different Kind of Love Story: Cormac McCarthy's / Olivia Carr Edenfield -- Selected Readings in the Genres of the American Novel -- Index.s
Includes bibliographical references and index.
Print version record.
Keywords: American fiction -- History and criticism; National characteristics, American, in literature; Literature and society -- United States; LITERARY CRITICISM -- American -- General; American fiction; Literature and society; National characteristics, American, in literature; United States; Electronic books; Criticism, interpretation, etc